Translational insights into the hormetic potential of carbon dioxide: from physiological mechanisms to innovative adjunct therapeutic potential for cancer - Gaspary, João Francisco Pollo; Edgar, Lee; Lopes, Luis Felipe Dias; Rosa, Carmen Brum; Siluk, Julio Cezar Mairesse (Frontiers in Physiology, 2024)
Background: Carbon dioxide (CO₂), traditionally viewed as a mere byproduct of cellular respiration, plays a multifaceted role in human physiology beyond simple elimination through respiration. CO₂ may regulate the tumor microenvironment by significantly affecting the release of oxygen (O₂) to tissues through the Bohr effect and by modulating blood pH and vasodilation. Previous studies suggest hypercapnia (elevated CO₂ levels) might trigger optimized cellular mechanisms with potential therapeutic benefits. The role of CO₂ in cellular stress conditions within tumor environments and its impact on O2 utilization offers a new investigative area in oncology.Objectives: This study aims to explore CO2's role in the tumor environment, particularly how its physiological properties and adaptive responses can influence therapeutic strategies.Methods: By applying a structured translational approach using the Work Breakdown Structure method, the study divided the analysis into six interconnected work packages to comprehensively analyze the interactions between carbon dioxide and the tumor microenvironment. Methods included systematic literature reviews, data analyses, data integration for identifying critical success factors and exploring extracellular environment modulation. The research used SMART criteria for assessing innovation and the applicability of results.The research revealed that the human body's adaptability to hypercapnic conditions could potentially inform innovative strategies for manipulating the tumor microenvironment. This could enhance O2 utilization efficiency and manage adaptive responses to cellular stress. The study proposed that carbon dioxide's hormetic potential could induce beneficial responses in the tumor microenvironment, prompting clinical protocols for experimental validation. The research underscored the importance of pH regulation, emphasizing CO2 and carbonic acid's role in modulating metabolic and signaling pathways related to cancer.The study underscores CO2 as vital to our physiology and suggests potential therapeutic uses within the tumor microenvironment. pH modulation and cellular oxygenation optimization via CO2 manipulation could offer innovative strategies to enhance existing cancer therapies. These findings encourage further exploration of CO2's therapeutic potential. Future research should focus on experimental validation and exploration of clinical applications, emphasizing the need for interdisciplinary and collaborative approaches to tackle current challenges in cancer treatment.